Respiratory arrest: a complication of cerebellar ectopia in adults. Issue 5 (May 1988) - Fish, D R; Howard, R S; Wiles, C M; Simon, L
Abstract : Two adult patients are described with cerebellar ectopia whose presentation at diagnosis was respiratory arrest. Following surgical decompression both patients become self ventilating and now lead independent lives. Cerebellar ectopia is a potentially remediable condition and should be considered in patients with unexplained respiratory arrest.